Spatial distribution vis-a-vis agglomeration of industry in Oromia Special Zone Surrounding Finfinne, Ethiopia - Tolerra, Milkessa Jagemma; Worku, Hailu (International Journal of Contemporary Economics and Administrative Sciences, 2024)
Manufacturing has long been a vital component of emerging countries’ economic development. Its relevance has been claimed in recent years to have decreased during the last 20-25 years, resulting in premature deindustrialization or non-industrialization in developing countries. This study explores the nature of spatial distribution and agglomeration of industry in Oromia Special Zone Surrounding Finfinne, Ethiopia. Firm stage facts set and distance-based method were used to answer research question. Besides, two sets of indications for service and industrialized firms were set correspondingly to adjust to the study in the intra-built up vicinity. Perhaps the most salient finding of the study indicates that the spatial pattern of most industries were agglomerated but not connected. Besides, the index of space-based clustering for manufacturing firm is more than 0.05, but approximately 0.03 for service firm.